Primeros registros de la tribu kingsleyini (Crustácea: decápoda: pseudothlphusidae) para Colombia - Rocha de Campos Martha Helena (Caldasia)
This is to report the first record for Colombia of two species of fresh-water crabs of the Kingsleyini Bolt, 1970 tribe. The species Prionothelphusa eliasi Rodríguez, 1980 and Orthothelphusa holthuisi (Rodríguez, 1967) had previously been recorded only for Venezuela. Se establece el primer registro para Colombia de la tribu Kingsleyini Bott, 1970, representado por las especies Prionothelphusa eliasi Rodríguez, 1980 y Orlhothelphusa holthuisi (Rodríguez, 1967). Estas especies solo habían sido registradas para Venezuela.